Genome-wide identification of BcGRF genes in flowering Chinese cabbage and preliminary functional analysis of BcGRF8 in nitrogen metabolism - Zhang, Shuaiwei; Li, Guangguang; Wang, Yudan; Anwar, Ali; He, Bin; Zhang, Jiewen; Chen, Changming; Hao, Yanwei; Chen, Riyuan; Song, Shiwei (Frontiers in Plant Science, 2023)
Growth-regulating factors (GRFs) are a unique family of transcription factors with well-characterized functions in plant growth and development. However, few studies have evaluated their roles in the absorption and assimilation of nitrate. In this study, we characterized the GRF family genes of flowering Chinese cabbage (Brassica campestris), an important vegetable crop in South China. Using bioinformatics methods, we identified BcGRF genes and analyzed their evolutionary relationships, conserved motifs, and sequence characteristics. Through genome-wide analysis, we identified 17 BcGRF genes distributed on seven chromosomes. A phylogenetic analysis revealed that the BcGRF genes could be categorized into five subfamilies. RT-qPCR analysis showed that BcGRF1, 8, 10, and 17 expression clearly increased in response to nitrogen (N) deficiency, particularly at 8 h after treatment. BcGRF8 expression was the most sensitive to N deficiency and was significantly correlated with the expression patterns of most key genes related to N metabolism. Using yeast one-hybrid and dual-luciferase assays, we discovered that BcGRF8 strongly enhances the driving activity of the BcNRT1.1 gene promoter. Next, we investigated the molecular mechanism by which BcGRF8 participates in nitrate assimilation and N signaling pathways by expressing it in Arabidopsis. BcGRF8 was localized in the cell nucleus and BcGRF8 overexpression significantly increased the shoot and root fresh weights, seedling root length, and lateral root number in Arabidopsis. In addition, BcGRF8 overexpression considerably reduced the nitrate contents under both nitrate-poor and -rich conditions in Arabidopsis. Finally, we found that BcGRF8 broadly regulates genes related to N uptake, utilization, and signaling. Our results demonstrate that BcGRF8 substantially accelerates plant growth and nitrate assimilation under both nitrate-poor and -rich conditions by increasing the number of lateral roots and the expression of genes involved in N uptake and assimilation, providing a basis for crop improvement.